Parents’ Involvement In Learning Assessment During Remote Learning In Pandemic Era - Haiyudi Haiyudi; Sittiphon Art-In (Universitas Negeri Malang, 2021)
Abstract: This study is aimed at providing an assessment scheme during learning at home by involving parents. Teachers as well as parents’ role in an intensive communication were emphasized under collaboration to help each other. The method used in this research was argumentative literature review on standard document of Panduan Penilaian oleh Pendidik dan Satuan Pendidikan (Kemendikbud, 2017). The purpose of this research is focusing on reducing teachers’ workload and confusion on how to assess students during learning at home. On the other side, it is to give an understanding of the importance of parental involvement. As a result, a new manipulated assessment scheme had been introduced in this research. It could be used not only during the Covid-19 pandemic but in a normal program of education. Lastly, the communication between parents and school should be well maintained in order to get the best result of students’ achievements as well.Abstrak: Penelitian ini bertujuan untuk memberikan skema penilaian baru selama pembelajaran jarak jauh (PJJ) dengan melibatkan orang tua. Peran guru dan orang tua dalam komunikasi intensif sangat ditekankan untuk meningkatkan hasil prestasi siswa. Metode yang digunakan dalam penelitian ini adalah kajian pustaka argumentatif terhadap dokumen Panduan Penilaian oleh Pendidik dan Satuan Pendidikan oleh Kemendikbud (2017). Kajian ini bertujuan untuk mengurangi beban kerja guru dan kebingungan tentang cara menilai siswa selama belajar di rumah serta mememberikan pemahaman tentang pentingnya keterlibatan orang tua. Hasilnya, skema penilaian yang dimanipulasi telah diperkenalkan dalam penelitian ini. Ini dapat digunakan tidak hanya selama pandemi Covid-19, tetapi juga dalam program pendidikan normal. Di sisi lain, komunikasi antara orang tua dan sekolah harus terus dijaga untuk mendapatkan hasil yang terbaik dari prestasi siswa